Improving Supply Chain Performance of a Start-Up Company: A Case Study of Avakino Limited - Muhammad Sani Adam; Tanimu Dandutse (ExcelingTech, 2023)
Effective supply chain management is critical for the success of a business, ensuring efficient and cost-effective delivery of products and services while minimizing risks and enhancing the customer experience. This paper presents a case study on Avakino Ltd's supply chain management, analyzing its nature, challenges, and proposed recommendations. The study reveals that Avakino Ltd has an agile and global supply chain, sourcing products from low-cost suppliers in Asia and Africa. However, the company faces challenges due to unreliable suppliers, low production capacity, and supply chain inefficiencies, hindering its aim of providing fast and high-quality products to customers. To address these issues, the study proposes a relationship-building strategy between Avakino Ltd and its suppliers, through long-term contracts, improved communication, and developing low production capacity suppliers through sourcing reliable Tier 2 suppliers. Implementing these recommendations can help Avakino Ltd maintain its competitive advantage and achieve its goal of delivering timely, affordable, and high-quality products to its customers.